Distribution of Radionuclides in Northern Rio Grande Fluvial Deposits near Los Alamos National Laboratory, New Mexico. - 20160731 frey50; Department of Energy Oversight Bureau, NM Environment Department (Santa Fe, NM State of New Mexico, 2007)
The New Mexico Environment Department's Department of Energy Oversight Bureau conducted a five year study to identify radionuclide contamination originating from teh Los Alamos National Laboratory (LANL) in abandoned channels, old flood plains, and other fluvial deposits along the Rio Grand. The highest proportions of LANL contaminants in sediments are nearest to the discharge sources. Sediment sorting by fluvial processes throughout the past 60 years contributed unexpected contaminant concentrations in White Rock Canyon.
NM H 600.82:D 58
Keywords: David Englert; Michael Dale; Kim Granzow; and Richard Mayer; Contamination - Los Alamos National Laborartory - New Mexico. -- Radionuclide contamination - New Mexico. -- Radionuclide contamination - White Rock Canyon - New Mexico -- Radionuclide contamination - Santa Clara Pueblo - New Mexico -- Radionuclide contamination - Canada Ancha - New Mexico -- Radionuclide contamination - Pajarito Canyon - New Mexico -- Radionulcide contamination - Water Canyon - New Mexico -- Radionuclide contamination - Otowi Bridge - Rio Grande confluence. -- Pollution - New Mexico